Existence of periodic solution for first order nonlinear neutral delay equations. (2001) - Wang, Genqiang; Yan, Jurang
Abstract : In this paper by using the coincidence degree theory, sufficient conditions are given for the existence of periodic solutions of the first order nonlinear neutral delay differential equation.